2014
DOI: 10.1371/journal.pone.0084986
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Behaviour in Presence of Non-UV-Irradiated Titanium Dioxide Nanoparticles

Abstract: Listeria monocytogenes is the agent of listeriosis, a food-borne disease. It represents a serious problem for the food industry because of its environmental persistence mainly due to its ability to form biofilm on a variety of surfaces. Microrganisms attached on the surfaces are a potential source of contamination for environment and animals and humans. Titanium dioxide nanoparticles (TiO2 NPs) are used in food industry in a variety of products and it was reported that daily exposure to these nanomaterials is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
(48 reference statements)
1
30
1
Order By: Relevance
“…EPS production and biofilm formation in the case of the bacterial consortium was higher as compared to the individual bacterial isolates in both light and dark conditions, though the difference was found to be statistically insignificant (p 40.05). A previous report showed that the biofilm mass formed in the presence of TiO 2 NPs appeared to increase in LM2 cultures at all nanoparticles doses utilized in a dose-dependent manner during 24 h incubations with significant values for 80, 8, and 0.8 mg/mL (Ammendolia et al, 2014). It has been shown that the presence of iron, especially FeCl 3 , enhances biofilm formation in P. aeruginosa (Patriquin et al, 2008;Borcherding et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…EPS production and biofilm formation in the case of the bacterial consortium was higher as compared to the individual bacterial isolates in both light and dark conditions, though the difference was found to be statistically insignificant (p 40.05). A previous report showed that the biofilm mass formed in the presence of TiO 2 NPs appeared to increase in LM2 cultures at all nanoparticles doses utilized in a dose-dependent manner during 24 h incubations with significant values for 80, 8, and 0.8 mg/mL (Ammendolia et al, 2014). It has been shown that the presence of iron, especially FeCl 3 , enhances biofilm formation in P. aeruginosa (Patriquin et al, 2008;Borcherding et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…Static biofilm assay was performed three times for individual bacteria and bacterial consortium, and the averages and standard error were calculated for the repetitions of all the experiment. All values were recorded after subtraction of the background absorbance of wells containing NPs (Ammendolia et al, 2014). Membrane permeability of treated cells and untreated cells was observed by fluorescence microscopy (Leica, DM-2500) after 2 h of TiO 2 NP interaction.…”
Section: Microtiter Plate Biofilm Production Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Increased biofilm production due to exposure to TiO 2 NP may favor bacterial survival in environment and its transmission to animal and human hosts (Ammendolia et al, 2014). Results from Tong et al (2013b) additionally revise simplified predictive relationship between photoactivity and phototoxicity of TiO 2 NP, underscoring the complexity of cellular reactions as provoked by TiO 2 NP exposure.…”
Section: Effects On Microorganismsmentioning
confidence: 99%
“…Whereas Dhandapani et al (2012) reported that TiO 2 NP, which were synthesized by B. subtilis, are phototoxic against B. subtilis biofilms, non UV-irradiated NP were found to influence EPS production and structural architecture of a listerial biofilm (Ammendolia et al, 2014). Increased biofilm production due to exposure to TiO 2 NP may favor bacterial survival in environment and its transmission to animal and human hosts (Ammendolia et al, 2014).…”
Section: Effects On Microorganismsmentioning
confidence: 99%